Impact of SBRT fractionation in hypoxia dose painting — Accounting for heterogeneous and dynamic tumor oxygenation. Issue 5 (14th April 2019) - Kjellsson Lindblom, Emely; Ureba, Ana; Dasu, Alexandru; Wersäll, Peter; Even, Aniek J. G.; van Elmpt, Wouter; Lambin, Philippe; Toma‐Dasu, Iuliana
Abstract : Purpose: Tumor hypoxia, often found in nonsmall cell lung cancer (NSCLC), implies an increased resistance to radiotherapy. Pretreatment assessment of tumor oxygenation is, therefore, warranted in these patients, as functional imaging of hypoxia could be used as a basis for dose painting. This study aimed at investigating the feasibility of using a method for calculating the dose required in hypoxic subvolumes segmented on 18 F‐HX4 positron emission tomography (PET) imaging of NSCLC. Methods: Positron emission tomography imaging data based on the hypoxia tracer 18 F‐HX4 of 19 NSCLC patients were included in the study. Normalized tracer uptake was converted to oxygen partial pressure ( p O2 ) and hypoxic target volumes (HTVs) were segmented using a threshold of 10 mmHg. Uniform doses required to overcome the hypoxic resistance in the target volumes were calculated based on a previously proposed method taking into account the effect of interfraction reoxygenation, for fractionation schedules ranging from extremely hypofractionated stereotactic body radiotherapy (SBRT) to conventionally fractionated radiotherapy. Results: Gross target volumes ranged between 6.2 and 859.6 cm 3, and the hypoxic fraction < 10 mmHg between 1.2% and 72.4%. The calculated doses for overcoming the resistance of cells in the HTVs were comparable to those currently prescribed in clinical practice as well as those previously tested in feasibility studies on dose escalation in NSCLC. Depending on the size of the HTV and the distribution of p O2, HTV doses were calculated as 43.6–48.4 Gy for a three‐fraction schedule, 51.7–57.6 Gy for five fractions, and 59.5–66.4 Gy for eight fractions. For patients in whom the HTV p O2 distribution was more favorable, a lower dose was required despite a bigger volume. Tumor control probability was lower for single‐fraction schedules, while higher levels of tumor control probability were found for schedules employing several fractions. Conclusions: The method to account for heterogeneous and dynamic hypoxia in target volume segmentation and dose prescription based on 18 F‐HX4‐PET imaging appears feasible in NSCLC patients. The distribution of oxygen partial pressure within HTV could impact the required prescribed dose more than the size of the volume.